Keterlambatan Penyerapan Anggaran: Peran Komitmen Organisasi Sebagai Moderasi - Ori Marsontio; Yesi Mutia Basri; Vince Ratnawaty (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2022)
The purpose of this line of research is to analyze the effects of planning violations, implementation of violations, quality of HR, administration, and documentation of procurement against delays in the absorption of violations by being moderated by the organization. The population in this study is OPD in Indragiri Hulu Regency which consists of 33 agencies. Respondents in this study were budget management officials taken as many as 3 people per OPD. Data were collected by sending questionnaires directly to respondents in the study. Data analysis with multiple regression and Moderate Regression Analysis shows that budget planning, budget execution, quality of human resources, administration, and procurement documents affect the delay budget absorption. Organizational commitment moderates the effect of planning violations, quality of human resources, administration, and procurement documents against delays in the absorption of violations. However, organizational commitment does not moderate the effect of budget execution on delays in budget absorption.